Confining Li⁺ Solvation in Core–Shell Metal–Organic Frameworks for Stable Lithium Metal Batteries at 100 °C - Nguyen, Minh Hai; Shin, Jeongmin; Kim, Mee‑Ree; Nguyen, Quan Van; Cha, JinHyeok; Park, Sangbaek (Nano-Micro Letters, 2026)
The practical deployment of lithium metal batteries remains severely constrained, especially under elevated temperatures. Although metal–organic frameworks (MOFs) improve the thermal stability of liquid electrolytes by capturing them in well-ordered sub-nanopores, interparticle voids between MOF particles readily absorb liquid electrolyte, obscuring our understanding of the intrinsic role of nanopores in directing Li⁺ transport. To address this challenge, we introduce a one-dimensional (1D) MOF model architecture that eliminates interparticle effects and enables direct observation of Li⁺ solvation and de-solvation dynamics. Comparative studies of 1D HKUST-1 and ZIF-8 uncover distinct transport behaviors, supported by both experimental measurements and neural network potential-based molecular dynamics simulations. Building on these insights, we construct a hierarchical core–shell MOF architecture by integrating ZIF-8 (core) and HKUST-1 (shell) onto a hybrid fiber scaffold. This design harnesses the complementary strengths of both MOFs to achieve continuous ion pathways, directional Li⁺ conduction, and improved thermal and electrochemical resilience. Highlights: 1 We report the in-situ growth of core–shell metal-organic frameworks on glass fiber, creating a binder-free quasi-solid-state electrolytes (QSSEs) with multiple Li+ transport pathways. 2 Pore-size-dependent solvation and de-solvation structures of Li+ are confined within HKUST-1 and ZIF-8 channels, enabling tailored ion dynamics. 3 The core–shell QSSE achieves high Li+ conductivity, suppressed dendrite growth, and stable Li plating/stripping under high-temperature conditions. 4 Lithium metal batteries with the core–shell QSSE show exceptional cycling stability at 100 °C.